THE INFLUENCE OF TRUST, INNOVATION AND SERVICE QUALITY ON CUSTOMER LOYALTY - Akmalia, Atika Firmanda; Supeni, Retno Endah; Izzudin, Ahmad (Univesitas Muhammadiyah Tangerang, 2025)
The problems that occur at Osing Barbershop, seen from the level of customer trust, innovation and quality of service indicate problems that need special attention, as well as the low level of customer loyalty at Osing Barbershop, from several factors it is necessary to conduct further research with the aim of increasing customer loyalty at Osing Barbershop. This study aims to determine and analyze the effect of trust, innovation and quality of service on customer loyalty at Osing Barbershop, Jember Regency. This type of research uses a quantitative method with a sample size of 195 respondents and uses the Non Probability Sampling sampling technique with a purposive sampling approach with the help of a questionnaire as the main tool in collecting respondent data. The data analysis technique for this study uses instrument testing, classical assumptions, multiple linear regression, hypotheses and coefficients of determination. The results of the analysis obtained show that trust, innovation and quality of service have a positive and significant effect on customer loyalty at Osing Barbershop, Jember Regency. The results of the f test have a simultaneous effect and the results of the R2 Determination Coefficient test with a contribution level of influence of 0.411 or 41%.